Production of Biogas from an Agro-industrial Waste and its Characteristics - Iqbal, K.; Aftab, T.; Iqbal, J.; Aslam, S.; Ahmed, R. (Journal of Scientific Research, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Molasses is a significant by-product of sugar industry and can be used as substrate in anaerobic digestion process for biogas production. Molasses was diluted ten time; inoculated by methane producing bacteria, mixed thoroughly in 2 liter batch bioreactor, kept at 370C for 15 days under anaerobic conditions for biogas yield. pH in the process was monitored three times a day. Total solids, volatile solids and COD were measured at alternate days. The gas production was measured by water displacement method. Ten times diluted molasses under anaerobic conditions, in the presence of methane producing bacteria was converted to 6.55 dm3/kg of biogas or 3.93 dm3/kg CH4 and 0.144 kWh electricity. Keywords: Agro industrial waste; Molasses; Methanogen; Anaerobic digestion; Biogas production. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i2.17320 J. Sci. Res. 6 (2), 347-357 (2014) <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –>